The Role of Inclusive Leadership in Supporting an Inclusive Climate in Diverse Public Sector Teams. (September 2021) - Ashikali, Tanachia; Groeneveld, Sandra; Kuipers, Ben
In organizations with a diverse workforce, inclusive leadership is assumed to be required to support the full appreciation and participation of diverse members. To date, studies identifying how leadership enables an inclusive climate in diverse teams are scarce. The aim of this study, therefore, is to examine how inclusive leadership fosters inclusiveness in diverse teams. Hypotheses were tested on a sample of 293 team members clustered in 45 public sector teams using structural equation modeling. The results showed that inclusive leadership positively moderates the negative relation between team ethnic–cultural diversity and inclusive climate. This study shows that greater team diversity does not automatically yield an inclusive climate. Inclusive leadership is needed to support an inclusive climate in which different team members are valued for what they bring to work practices. Inclusive leadership is crucial for fostering inclusiveness in diverse teams. Limitations are discussed and recommendations for future research are proposed.